2000
DOI: 10.1007/bf02990476
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of myocardial18F-fluorodeoxyglucose positron emission computed tomography in dilated cardiomyopathy and ischemic cardiomyopathy

Abstract: Myocardial 18F-fluoro-2-deoxyglucose (FDG) positron emission tomography (PET) has been used to assess myocardial ischemia and viability, but few studies have conducted on FDG-PET for dilated cardiomyopathy (DCM). We investigated myocardial FDG uptake in patients with DCM in comparison with ischemic cardiomyopathy (ICM). Twenty-four patients with heart failure were included in this study. Fourteen of them were diagnosed as DCM and the other 10 were ICM. All of them underwent myocardial FDG-PET at fasting and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Yamaguchi et al [73] investigated regional myocardial 18 F-FDG distribution with injection during fasting and following glucose loading in patients with heart failure due to IDC or postischemic LV dysfunction. In 7/14 IDC patients and 10/10 ischemic patients, regional FDG uptake was seen with fasting.…”
Section: Myocardial Blood Flow and Glucose Uptakementioning
confidence: 99%
“…Yamaguchi et al [73] investigated regional myocardial 18 F-FDG distribution with injection during fasting and following glucose loading in patients with heart failure due to IDC or postischemic LV dysfunction. In 7/14 IDC patients and 10/10 ischemic patients, regional FDG uptake was seen with fasting.…”
Section: Myocardial Blood Flow and Glucose Uptakementioning
confidence: 99%
“…By contrast, there have been only a few FDG-PET studies in idiopathic dilated cardiomyopathy (DCM). Some of them have shown that FDG-PET is useful in differentiating between idiopathic DCM and ischemic cardiomyopathy (5) and that inhomogeneous glucose metabolism predicts a poor outcome in DCM (6).…”
mentioning
confidence: 99%
“…Left ventricular dilatation following myocardial infarction is a harbinger of the development of heart failure and left ventricular endsystolic volume index is a strong predictor or mortality. Patients with LVEF <30% and left ventricular end-systolic volume index >100 ml/m 2 have a 5-year survival of 54% [7]. Furthermore, increased preoperative left ventricular size predicts a poor outcome following CABG patients with preoperative ejection fractions <30% and a left ventricular end-systolic volume index >100 ml/m 2 have a 5-year survival of only 54% [8].…”
Section: Discussionmentioning
confidence: 95%
“…Randomized testing is underway in the STICH trial, and the Cleveland Clinic re-establishes its vital importance by mirroring their 1978 report regarding the VA Hospital CABG trial [7]. The prior question investigated if a closed artery should be opened, whereas this article tests a comparable biologic principle by surveying mechanical changing of a diseased sphere into conical form with restoration.…”
Section: Editorial Commentmentioning
confidence: 97%